Early sport practice is related to lower prevalence of cardiovascular and metabolic outcomes in adults independently of overweight and current physical activity - Fernandes, Romulo Araujo [UNESP]; Zanesco, Angelina [UNESP] (Elsevier B.V., 2015)
Background and objective: Early sport practice prevents development of diseases in children/adolescents, but still unclear its effect over health in adulthood. Therefore, the purpose of this study was to analyze the association between sport practice in early life and chronic diseases in adulthood. Materials and methods: A retrospective population-based survey carried out in eight Brazilian cities with adults of both genders. Throughout a multistage random process 2720 adults (1096 male and 1624 female) were selected and interviewed. Type 2 diabetes mellitus and arterial hypertension were assessed in a face-to-face interview through a self-report, which was necessarily based on previous medical diagnosis. Early sport practice was assessed in childhood (7-10 years old) and adolescence (11-17 years old). Current physical activity and body mass index were assessed in adulthood throughout a face-to-face interview. Results: Type 2 diabetes mellitus and arterial hypertension were identified in 8.1% (95% CI, 7.1-9.2) and 23.5% (95% CI, 21.9-25.1) of the sample, respectively. Early sport practice during childhood and adolescence was associated with lower occurrence of arterial hypertension (OR, 0.49; 95% CI, 0.33-0.73) and type 2 diabetes (OR, 0.46; 95% CI, 0.24-0.88) in adulthood. Conclusions: Independently of obesity and current physical activity, early sport practice in early life was positively associated with lower occurrence of chronic diseases in adulthood. (C) 2015 Lithuanian University of Health Sciences. Production and hosting by Elsevier Sp. z o.o. This is an open access article under the CC BY-NC-ND license.
Keywords: Adolescents; Epidemiology; Sport medicine; Metabolism